2015
DOI: 10.1002/ppul.23367
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of lung function in children with sickle cell disease

Abstract: Lung function deteriorated with increasing age in SCD children and the rate of decline was greater in younger children in whom ACS episodes were more common. Pediatr Pulmonol. 2016;51:717-723. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 39 publications
5
37
0
4
Order By: Relevance
“…Longitudinal studies have shown that there is a decline in lung volume and pulmonary function over the years in children with SCD; however, the pathophysiology of respiratory disorders in childhood has not been fully elucidated 9 35 This decline was reported in a cohort study by Lunt et al, 36 who demonstrated that a history of ACS episodes was the only independent factor associated with reduced lung volumes. Some biological markers, such as leukocytosis, are known to be associated with SCD severity, but their relationship with pulmonary function has only recently been the subject of investigation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have shown that there is a decline in lung volume and pulmonary function over the years in children with SCD; however, the pathophysiology of respiratory disorders in childhood has not been fully elucidated 9 35 This decline was reported in a cohort study by Lunt et al, 36 who demonstrated that a history of ACS episodes was the only independent factor associated with reduced lung volumes. Some biological markers, such as leukocytosis, are known to be associated with SCD severity, but their relationship with pulmonary function has only recently been the subject of investigation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The lung is often affected in sickle cell disease (SCD), acutely with acute chest syndrome (ACS) (1) and chronically with dyspnea and reduced exercise capacity (2,3), loss of lung function (4,5), and pulmonary hypertension (6). Studies have sought to define pulmonary function abnormalities in children and adolescents with SCD (4, 7-13) using pulmonary function evaluations conducted when children and adolescents were at their baseline status, with tests most often obtained in clinical laboratories during routine care.…”
mentioning
confidence: 99%
“…The estimated prevalence of obstructive lung disease in SCD children ranges from 8% to 57%, independent of a diagnosis of asthma (Table ) . Young children appear to have an obstructive pattern of lung disease while restrictive and diffusion defects are more commonly seen in older children and adults . Further, in the study by Maclean et al lung function in children with SCD was noted to decline over time at a rate of 3% decline in forced expiratory volume in 1 sec (FEV1) per year, a decline more rapid than in children with asthma .…”
Section: Sickle Cell Disease Acute Chest Syndrome and Asthmamentioning
confidence: 99%